Output Feedback Adaptive Sliding Mode Control Design for a Plate Heat Exchanger - Al-samarraie, Shibly Ahmed; Ali, Luma F. (Al-Nahrain Journal for Engineering Sciences, 2018)
The heat exchanger is a device used to transfer heat energy between two fluids, hot and cold. In this work, an output feedback adaptive sliding mode controller is designed to control the temperature of the outlet cold water for plate heat exchanger. The discontinuous gain value of the sliding mode controller is adapted according to a certain adaptation law, where the only information required is the measurement of the outlet cold temperature. A sliding mode differentiator was design to estimate time derivative of outlet hot water temperature. Two constraints which imposed on the volumetric flow rate of the hot water (control input) were considered within the rules of the proposed adaptation law in this work. These are the control input is positive only and has a maximum value. For constructing the sliding variable, the outlet hot water temperature and its time derivative are required. The maximum allowable desired outlet cold water has been estimated as function of heat exchanger parameters and maximum control input. The simulation results demonstrate the performance of the proposed adaptive sliding mode control where the outlet cold water was forced to follow desired temperature equal to . Additionally, the robustness of the proposed controller was tested for the case where the cold inlet temperature is not constant. The results reveal the robustness of the proposed controller.